Bimbingan Teknis Pengelolaan Forum Diskusi Web KIM Nusantara Pengurus KIM NAS Community DIY - Erfanti Fatkhiyah; Haryani, Prita (DHARMA BAKTI, 2023)
KIM Nusantra is an organization engaged in the field of information management, so it requires facilities to communicate and manage organizational administration. To facilitate management, a web was created to accommodate all needs from the central to regional levels, so to improve admin capabilities in managing the web, especially discussion forums, technical guidance on managing the KIM Nusantara web discussion forum is needed. Technical guidance on the management of discussion forums on the KIM Nusantara web is attended by KIM Community DIY management and is carried out offline, so that it is more optimal in providing explanations and hands-on practice using computers. Keywords: KIM Nusantara Web, technical assistance, web discussion forums, KIM Community